Mathematics Problem Solving Ability In Pontianak Private High School Level Quiziz Game - Hengki, Marianus; Yani T, Ahmad (JPMI (Jurnal Pendidikan Matematika Indonesia), 2024)
The ability to solve mathematical problems on Quizzizz illustrates that the data obtained from this research is used as a reference in writing reports. Learning through quizizz can also make students' motivation higher because the games played can be varied using game techniques. To keep up with existing developments, the ability to solve mathematical problems on Quizizz is seen from how high, medium and low ability is. This research describes abilities of Pontianak Private High School students in the context of using the Quizizz application as a learning medium. With a descriptive qualitative approach, this research involved students from a private high school in Pontianak who were given Quizizz as an assessment in mathematics learning. Data was obtained through direct observation, interviews, and giving Quizizz to students. The results of the data obtained were that high problem solving ability was 14.28%, medium ability was 48.57%, and low ability was 37.14%. The research results show that using Quizizz can improve students. Data analysis revealed three categories of problem solving ability, namely high, medium and low, based on the results of working on Quizizz. Likewise, planning problem solving plays a vital role in improving problem solving abilities. Students with high abilities are able to motivate themselves, while students with moderate abilities need a planning and motivation process to achieve high abilities.Applying design in problem solving is also a determining factor. Students with high abilities can implement designs well, requiring collaboration of understanding and ideas. Meanwhile, students with moderate abilities need designs that are strong in ideas. This category is described through the stages of problem solving, including understanding the problem, planning a solution, implementing the design, and checking again. So Quizizz is here to get rid of the threat of students solving mathematical problems.